A brief history of British drug policy: 1850-1950. Issue 2 (7th July 2020) - Yates, Rowdy
Abstract : Purpose: As the clamour within the drug treatment field in the UK – and throughout much of Europe – increases, leading agencies are arguing for a review of the current legislation and a change in focus away from criminal justice and towards a more public health understanding of addiction. Therapeutic communities have found themselves united with many drug users-led campaigns to argue for a wholesale restructuring of the legislative, policy and funding arrangements which recognises the role of recovery-oriented interventions within the mix. Given these on-going debates, it is perhaps useful to understand how the current arrangements were established [1 ]. Design/methodology/approach: In 1850s, the sale of opium – like alcohol – was largely unregulated. It was widely used, in a variety of preparations, by all classes for medical and non-medical purposes. A pennyworth of opium was as likely (perhaps more likely) as a pound of potatoes to find its way into the weekly shopping basket. Findings: By the 1920s, the Fu Manchu novels of Sax Rohmer – with their tales of innocent English virgins being seduced into crime and sexual perversion by an evil Chinese genius who lurked within the opium dens of Edwardian Britain – had redefined opium as a drug of the outside, the deadly, an agent in the enslavement of innocence. Originality/value: This dramatic change was largely brought about by the introduction of an array of new medications and a move away from traditional "herbal" remedies. This change was accelerated by the experiences of the First World War and underpinned by the print media and laid the foundations of the legislation and policy of the present day.